Penerapan Konsep Therapeutic Space Pada Healing and Rehabilitation Center di Ubud, Kabupaten Gianyar, Bali: Bahasa Indonesia - I Gede Damarutha Adrian Nugraha Arsitektur; I Wayan Wirya Sastrawan; Ni Putu Ratih Pradnyaswari Anasta Putri; Ni Komang Indra Mahayani (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2024)
Mental disorders are a condition of a person who experiences deviations in the person's thinking process, feelings and behavior. In Bali, especially in the Ubud area which is a tourism area in Bali, efforts have been made to deal with mental health cases. However, unfortunately, the number of rehabilitation facilities for mental health in Bali is less visible, when compared with rehabilitation facilities for narcotics and social rehabilitation. Therefore, the author attempts to design a container or building called the